SIKAP WISATAWAN NUSANTARA TERHADAP PRODUK WISATA KULINER DI KOTA PALEMBANG (Jurnal Ilmiah Pariwisata, 2015)
The objective of this research is to present a comprehensive framework of tourist attitude toward culinary tourism product in Palembang City. This research is using quantitative method with ex-post facto and longitudinal approach. Samples are taken during the high season and low season. Descriptive and inferential statistic conducted to analyze the research questions and the results are: 1) Knowledge, understanding, and tourist tendency toward culinary tourism in Palembang City tend to be positive. 2) Tourist attitude towards culinary in Palembang according to origin, age, and tourist destinations, as well as visit frequency did not differ significantly.